Correlation between Helicobacter pylori Infection and Metabolic Abnormality in General Population: A Cross-Sectional Study - Li-juan Lu; Ning-Bo Hao; Jian-Jun Liu; Xue Li; Rui-Ling Wang (Gastroenterology Research and Practice)
Background. Previous studies have suggested a link between Helicobacter pylori (H. pylori) and metabolic abnormality. This study aimed at investigating the correlation between H. pylori infection and metabolic abnormality in a general population. Methods. All enrolled participants underwent a carbon-13 urea breath test (13C-UBT). For each individual, the following data were collected: age, gender, alanine transaminase (ALT), total protein, albumin, cholesterol, triglyceride (TG), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), urea nitrogen, creatinine, uric acid, fasting plasma glucose, postprandial blood sugar, nonalcoholic fatty liver disease (NAFLD), and bone mineral density (BMD). Results. The study included 1867 (393 females and 1474 males, aged 54.0 ± 9.6 years) people that took a physical examination. There was no significant difference in gender and age between the study participants with and without H. pylori infection. The statistical data are as follows: albumin: P=0.045, uric acid: P=0.025, fasting glucose: P=0.043, and postprandial blood glucose: P=0.035. In terms of the patients with NAFLD, there were significant differences in ALT and HDL-C between the study participants with and without H. pylori infection. TG (P=0.048), HDL-C (P=0.011), and fasting blood glucose (P=0.018) were significantly different in both groups among individuals who got osteopenia. Conclusion. H. pylori infection may be an important factor affecting metabolic abnormality and osteoporosis.